ANALISIS YURIDIS TERHADAP KETERANGAN AHLI DALAM TINDAK PIDANA NARKOTIKA (STUDI PUTUSAN NOMOR:4/PID.SUS/2019/PN.BRB) - Bimar Prananta; Dian Adriawan Daeng Tawang (Reformasi Hukum Trisakti, 2022)
Verdict Number 4/Pid.Sus/2019/PN Brb (hereinafter reffered as the Verdict) is a narcotics crime case with the defendant Achmad Syarif. The defendant submitted expert testimony, Sofyan Nata Saragih who testified that he had examined the defendant and diagnosed him with Accute Psychotic Schizophrenia Disorder. The Verdict stated the defendant was healthy and his actions could be accounted before the law. This is a problem because expert examination is not dan accordance with applicable regulations. The problems: whether expert testimony dan the Verdict is dan accordance with the applicable laws and regulations and is the Verdict which imposed criminal sentence on the defendant dan accordance with laws and regulations. The purpose of this research is to describe and analyze the Verdict. The research is a normative legal research, using secondary data and analyzed qualitatively. The lack of laws and regulations regarding expert testimony has impact on the wrong decision of the judge dan imposing a criminal sentence on the defendant. It is hoped that DPR can revise KUHAP by presenting 1 clear article regarding the conditions for person to become expert dan criminal case. It is considered necessary for judge to apply Article 180 of KUHAP and Article 19 concerning Mental Health.